The Rationale for Determining the Level of the Minimum Retirement Age - Jedynak, Tomasz (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2017)
The study examines the principles of determining the minimum retirement age as one of the primary parameters of retirement systems. The main purpose of the article is to contribute the following to the ongoing debate on the official retirement age: methodical considerations, historical perspective and critical analysis of arguments which are put forward within the context of rising and equalising retirement age for women and men. Based on a review of the literature, epistemological considerations and also drawing on the latest empirical data, the role of the retirement age in modern old-age security systems was analysed. The arguments formulated for raising and equalising the retirement age for men and women are also discussed. The thesis proper of the paper is that the current socio-economic changes prompt the need to modify the previous approach to the age at which individuals end their professional activity. The analysis presented in the paper justifies this contention. However, the changes to the previous approach cannot be arbitrary, isolated from complex social policy or realise only short-term political goals.